PUBLIC MANAGEMENT OF THE DEVELOPMENT OF THE MACHINE-BUILDING COMPLEX OF UKRAINE IN THE CONDITIONS OF ECONOMIC INSTABILITY - Shchur, R. I.; Tkachuk, D. Yu. (The actual problems of regional economy development, 2024)
The article proves that the machine-building complex is, was and remains a basic segment of the national economy and industry, in particular, because it has sufficient production and resource potential and human capital for effective functioning and providing the needs of the economy with the necessary range of machine-building products. However, there is a need to improve the implementation of state policy and public management of the development of the machine-building complex of Ukraine. The purpose of the article is to study the public management of the development of the machine-building complex of Ukraine in conditions of economic instability and to determine the effectiveness of management decision-making regarding the stimulation of the state policy of the development of this industry. The research carried out in the article showed that the main causes of destructive changes in the machine-building complex of Ukraine (except for the military aggression of the Russian Federation with the corresponding consequences) were: a) neglect of national economic interests in the implementation of state management (based on the position of international competitiveness and the strategic importance of the development of machine-building), primarily in the agreements on accession to the WTO and the Free Trade Agreement with the EU, as well as other documents on the liberalization of foreign trade related to this segment of the industry; b) ineffective state policy to create favorable, motivational and stimulating conditions for attracting capital investments in machine-building production and optimizing its connections with other sectors of the economy, in particular to meet domestic demand for relevant products. Also, it was established that the formation and implementation of strategic principles for the improvement of public management in the machine-building complex is necessary for Ukraine today. The development of a complex of organizational measures will contribute to achieving results in the field of technological modernization and increasing the competitiveness of machine-building enterprises. Such strategic decisions should take into account the global trends of innovative development, contribute to the development of international relations, the creation of cooperative projects in this area, as well as the increase of defense capability and national security based on the implementation of effective state policy and management.